Design and Implementation of the Instrumentation and Sensor System for testing of a sub modelled 10 MW offshore superconducting wind turbine. (April 2019) - Ramalingam, R; Sun, J; Neumann, H
Abstract: The large head mass of an offshore wind turbine can be reduced by using superconducting technology. As a proof of concept, a superconducting 10 MW wind turbine for offshore application is investigated under the SUPRAPOWER project funded by EU-FP7. SC coils were developed using MgB2 tapes and cooled to 20 K by a two stage Gifford McMahon cryocooler in a modular rotating cryostat. To study the coil performance and to measure and control the sub model, a LABVIEW based instrumentation system is developed. To measure the temperature distribution in a rotating cryostat, an optical based sensing system is designed and introduced. The effect of rotation on an optical based sensing system is studied. In this paper, the instrumentation along with the thermal characteristics and validation of the optical sensing system for rotating machines and its installation techniques will be reported.